The Elusive Hedge: Crypto Correlation Dynamics in Global Stock/Index Bull/Bear Markets - Arief Rachmansyah; Nugraha Nugraha (Politeknik Siber Cerdika Internasional, 2026)
Background: The integration of cryptocurrencies into regulated investment channels has intensified the need to test whether their diversification value survives market stress. Objective: This study evaluates regime-dependent cryptocurrency–equity correlations at index and individual-stock levels across seven developed and emerging markets. Methods: Weekly returns comprise 522 Bitcoin observations, 490 Ethereum observations, seven national indices, and 250 constituent stocks. A 20% directional-change algorithm identifies all bullish and bearish episodes. Pearson correlations are complemented by Spearman coefficients, Fisher r-to-z tests, and 10,000 paired circular-block bootstrap replications. Results: All 14 index–cryptocurrency and 500 stock–cryptocurrency correlations are below |0.40| in bullish regimes. Robust regime changes occur in 3/14 index pairs and 74/500 stock pairs; 71 stock correlations are higher in bearish regimes and three are lower. The index evidence is concentrated in Bitcoin linkages with Brazil, South Africa, and the United States. Conclusion: Cryptocurrencies are conditional diversifiers rather than universal hedges. Investors and portfolio managers should monitor regime-specific correlations and stress-test crypto exposure instead of relying on static diversification assumptions.